Development and Validation of a Scale to Collect Student Perceptions About Formative Assessment in the Mathematics Classroom - Broch, Alejandra Balbi (2025)
Despite the critical role of formative assessment (FA) in teaching and learning, there are few instruments that enable its evaluation from students’ perspective in mathematics education. We aimed to develop and validate a scale to collect secondary education students’ perspective of the FA practices developed by their teachers in mathematics class. The instrument was designed starting from a rational criterion, followed by content and face validity evidence analysis. Then, the internal structure was studied through an exploratory factor analysis (N = 534), and a second-order solution was reached that preserved 24 items distributed in four first-order dimensions (collaborative learning, formative feedback, responsive teaching,and students’ reflection) and a general factor. This structure was verified by confirmatory factor analysis (N = 1,943). The final version of the instrument was examined regarding its factorial invariance and temporal stability. The scale promotes teachers’ and students’ involvement in collaborative dynamics and evaluation of mathematics learning environments.